TEACHERS' STRATEGIES IN TEACHING READING TO STUDENTS AT SECONDARY LEVEL - Dewi, Kusumah Noor (2016)
The study analyzed the teachers' strategies in teaching reading to students at secondary level. Qualitative approaches was employed in this study. The participants of this study were two English teachers and two clases of students in one of state junior high school in Bandung. This study used three techniques in collecting data: classroom observation, interview, and questionnaire. The findings revealed that there were seven strategies employed by the teachers: silent reading, reading aloud, skimming and scanning, taking notes, highlight, translating, and summarizing. In addition, the result of the study also showed students' positive responses. The result of the study is expected to the next researchers who associated with this field.;--- Penelitian ini dibuat untuk menganalisa strategi-strategi guru yang digunakan ketika mengajar siswa membaca pada tingkat SMP. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Responden yang dilibatkan dalam penelitian ini adalah 2 guru bahasa Inggris dan dua kelas di sebuah Sekolah Menengah Pertama di Kota Bandung. Penelitian ini menggunakan tiga teknik dalam mengumpulkan data, observasi kelas, wawancara, serta kuisioner. Hasil yang didapat setelah dilakukan penelitian menunjukan bahwa terdapat tujuh strategi yang sering digunakan oleh guru-guru, yaitu: membaca dalam hening, membaca keras, membaca sekilas dan menbaca teliti, menulis hal-hal penting, menandai hal-hal yang dianggap penting, menterjemah, dan menarik kesimpulan. Selain itu, hasil dari penelitian ini juga menunjukan respon yang positif pada siswa.